culture.pl - Uniwersytet im. Adama Mickiewicza w Poznaniu - Instytut Historii Sztuki (2014)
[Dt.:] Ziel des Internetportals ist die Förderung und Verbreitung polnischer Kultur im Ausland. Die Seite bietet einen Kulturkalender, ein Archiv zu polnischen Künstlern, Informationen zu jährlich stattfindenden Veranstaltungen (u.a. Festivals, Wettbewerbe), eine Adressenliste mit Museen, Galerien, Philharmonien, Theatern, Kunsthochschulen, anderen Kunstinstitutionen, wie auch Stiftungen, Vereinen und anderen Organisationen. Derzeit ist das Portal in polnischer und englischer Fassung zugänglich. - [Engl.:] The website www.culture.pl, created in the year 2001, is managed by the Adam Mickiewicz Institute (AMI) - a government cultural institution. One of AMI's missions is to promote Polish culture throughout the world, in particular by compiling and updating an integrated system of information about Polish culture and disseminating this information - in Polish and in English languages. It contains information on exhibitions, art fairs, galleries, artists, museums and other cultural institutions.